Cursed - Book 2 - Meyer, Marissa (New York : Feiwel and Friends, 2022)
"Adalheid Castle is in chaos. Following a shocking turn of events, Serilda finds herself ensnared in a deadly game of make-believe with the Erlking, who is determined to propel her deeper into the castle's lies. Meanwhile, Serilda is determined to work with Gild to help him solve the mystery of his forgotten name and past. But soon it becomes clear that the Erlking doesn't only want to use Serilda to bring back his one true love. He also seeks vengeance against the seven gods who have long trapped the Dark Ones behind the veil. If the Erlking succeeds, it could change the mortal realm forever. Can Serilda find a way to use her storytelling gifts for good--once and for all? And can Serilda and Gild break the spells that tether their spirits to the castle before the Endless Moon finds them truly cursed? Romance and adventure collide in this stunning finale to the Rumpelstilskin-inspired fairy tale."--
Keywords: Rumpelstiltskin (Folk tale) -- Adaptations; Rumpelstiltskin (Folk tale) -- Adaptations; Blessing and cursing -- Juvenile fiction; Truthfulness and falsehood -- Juvenile fiction; Kings and rulers -- Juvenile fiction; Secrecy -- Juvenile fiction; Good and evil -- Juvenile fiction; Blessing and cursing -- Fiction; Honesty -- Fiction; Kings, queens, rulers, etc. -- Fiction; Secrecy -- Fiction; Good and evil -- Fiction; Fantasy fiction